Technologically Dense Environments: What For? What Next? - Bruni, Attila; Pinch, Trevor; Schubert, Cornelius (Tecnoscienza – Italian Journal of Science & Technology Studies, 2013)
This conversation stems from and relies on the lectures presented by the three authors at the second STS Italia Summer School (2013 June 12-14, Ostuni, Italy). The text by Attila Bruni portrays in an impressionistic (and partly ironical) way the "genesis and development of a scientific fact", namely technologically dense environments (TDEs), sketching some of its basic characteristics and antescedents. Trevor Pinch, again in a personal anecdotal style, offers various examples of mundane interactions with technologies in dense and less dense environments, underlining how sociomateriality must always be unpacked, beside any innate or transformative properties of the materials themselves. Cornelius Schubert, finally, rather than closing the conversation, offers a case in point, focusing on improvisations in TDEs and, in particular, in medical practice.